Managing IT offshore projects in the Philippines prospectives and strategies through scenario building - Ramos, Roderick (Quezon City University of the Philippines Diliman, 2010)
Along with the increasing growth of BPO offshoring sector in the Philippines is the increasing role of technology project managers in managing offshore IT projects. Using the techniques in scenario building, the paper reveals that communication (e.g. language and culture), advancement in technology (e.g. cloud computing and security), project governance and control (e.g. empowerment, virtual teams), demand for Philippine services (e.g. weak US/EU economy, appeal for local insourcing), changing business models (e.g. customer trends), and emergence of China and India as regional powers are the six vital issues or challenges in managing IT offshore projects in 2020. Using the same vital issues, responses from the subject matter experts (SMEs) interviewed in this paper identified two issues that Philippine offshoring should watch-out, these are : (1) uncertainties in changing business models implemented by host companies as they try to respond to competition and changing business environment and (2) innovation and advancement in technology that will surely change the way offshore projects are managed in the future, particularly in year 2020. Employing the scenario building techniques, the paper identified the desired "future" for the management of IT offshoring projects and called it as "The Golden Era", where present policies of the government led to stronger BPO industry, demonstrated management skills by Filipino workforce elevated the Philippines to higher value-added services, and wind-fall revenues that came from the industry were used to research and development for further improvement of the industry. Recommendations and actions are identified to increase the probability of meeting the desired future should the government pursues this direction.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Information technology projects -- Philippines; Strategic planning